2013
DOI: 10.5194/bg-10-6759-2013
|View full text |Cite
|
Sign up to set email alerts
|

A new model for biomineralization and trace-element signatures of Foraminifera tests

Abstract: Abstract. The Mg / Ca ratio of Foraminifera calcium carbonate tests is used as proxy for seawater temperature and widely applied to reconstruct global paleo-climatic changes. However, the mechanisms involved in the carbonate biomineralization process are poorly understood. The current paradigm holds that calcium ions for the test are supplied primarily by endocytosis of seawater. Here, we combine confocal-laser scanning-microscopy observations of a membrane-impermeable fluorescent marker in the extant benthic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
137
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(152 citation statements)
references
References 22 publications
14
137
1
Order By: Relevance
“…These culture studies suggest that when only intrinsic intra-test variability is considered, the RSD is ∼ 30 % for Mg/Ca, compared to ∼ 8 % for Sr/Ca (values for all chambers analysed with a LA-ICP-MS; de Nooijer et al, 2014a). This difference between intrinsic intra-test variability in Mg/Ca and Sr/Ca was explained by the fact that during biomineralization processes, unlike Sr, Mg is strongly discriminated against in the calcifying fluid, and that these processes may vary over time and/or position in the test Erez, 2005, 2006;Nehrke et al, 2013;de Nooijer et al, 2014b). In some field studies (Allison and Austin, 2003;Curry and Marchitto, 2008), values for Mg/Ca intratest variability were similar to those observed in the culturing experiment, whereas only a single field study (Raitzsch et al, 2011) reported substantially higher Mg/Ca intra-test variability, with an RSD of 51 %.…”
Section: Approach For Estimating (Intrinsic) Intra-test Variability Imentioning
confidence: 99%
“…These culture studies suggest that when only intrinsic intra-test variability is considered, the RSD is ∼ 30 % for Mg/Ca, compared to ∼ 8 % for Sr/Ca (values for all chambers analysed with a LA-ICP-MS; de Nooijer et al, 2014a). This difference between intrinsic intra-test variability in Mg/Ca and Sr/Ca was explained by the fact that during biomineralization processes, unlike Sr, Mg is strongly discriminated against in the calcifying fluid, and that these processes may vary over time and/or position in the test Erez, 2005, 2006;Nehrke et al, 2013;de Nooijer et al, 2014b). In some field studies (Allison and Austin, 2003;Curry and Marchitto, 2008), values for Mg/Ca intratest variability were similar to those observed in the culturing experiment, whereas only a single field study (Raitzsch et al, 2011) reported substantially higher Mg/Ca intra-test variability, with an RSD of 51 %.…”
Section: Approach For Estimating (Intrinsic) Intra-test Variability Imentioning
confidence: 99%
“…This suggests that the incorporation of these cations is influenced by similar 420 biomineralization mechanisms, related to seawater vacuolization (Erez, 2003;Bentov and Erez, 2006), 421 trans-membrane transport of elements (Nehrke et al, 2013) and/or metastable precursor phases (Jacob 422 et al, 2017). The relative contributions of these mechanisms might differ between species, resulting in 423 the observed differences in element incorporation between species.…”
Section: For 409mentioning
confidence: 99%
“…For some other elements, including Mg and Sr, incorporation has been shown to be interdependent (e.g., Mewes et al, 2015). Such interdependency, however, varies between pairs of elements and is explained by a combination of simultaneous fractionation by the same process (e.g., Langer et al, 2016) and by involvement of different processes during calcification (Nehrke et al, 2013). These models and experimental results may imply that the incorporation of Ba could also be influenced by these physiological processes and/or the same fractionation process during calcite precipitation (e.g., through lattice distortion; Mucci and Morse, 1983;Mewes et al, 2015).…”
mentioning
confidence: 99%